A Comparison of Complications in Therapeutic versus Contralateral Prophylactic Mastectomy Reconstruction: A Paired Analysis. Issue 5 (2nd March 2022) - Sergesketter, Amanda R.; Marks, Caitlin; Broadwater, Gloria; Shammas, Ronnie L.; Greenup, Rachel A.; Clancy, Sharon; Plichta, Jennifer K.; Hollenbeck, Scott T.; Phillips, Brett T.
Abstract : Background: Although breast reconstruction after bilateral mastectomies including a contralateral prophylactic mastectomy is known to have a higher overall complication profile, whether reconstructive complication rates differ between the therapeutic mastectomy and contralateral prophylactic mastectomy sides remains unclear. Methods: Women undergoing bilateral mastectomies with autologous or implant-based breast reconstruction for a unilateral breast cancer at a single institution were identified (2009 to 2019). Postoperative complications were stratified by laterality (therapeutic mastectomy versus contralateral prophylactic mastectomy). Paired data were analyzed to compare the risks of complications between prophylactic and therapeutic reconstruction sides in the same patient. Results: A total of 130 patients (260 reconstructions) underwent bilateral autologous or implant-based reconstruction. Although most women underwent a simple mastectomy, a higher proportion of therapeutic mastectomies were modified radical mastectomies including axillary lymph node dissections compared to contralateral prophylactic mastectomies (15.4 percent versus 0 percent). Forty-four percent of women completed postmastectomy radiation therapy of the therapeutic side before definitive reconstruction. Overall, both therapeutic and prophylactic reconstructions had a similar incidence of reconstructive failure ( p = 0.57), return to the operating room ( p = 0.44), mastectomy skin flap necrosis ( p = 0.32), seroma ( p = 0.82), fat necrosis ( p = 0.16), wound infection ( p = 0.56), and cellulitis ( p = 0.56). Nearly one-fifth of patients experienced complications limited to the prophylactic side [contralateral prophylactic mastectomy reconstruction complications, n = 26 (20.0 percent); therapeutic mastectomy reconstruction complications, n = 15 (11.5 percent)]. Conclusion: Despite a history of local radiation therapy and more extensive oncologic surgery on the therapeutic side, there are no significant differences in the incidence of postsurgical complications on the therapeutic mastectomy and contralateral prophylactic mastectomy sides after bilateral reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.